2017
DOI: 10.1016/j.clnu.2015.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Intradialytic parenteral nutrition in maintenance hemodialysis patients suffering from protein-energy wasting. Results of a multicenter, open, prospective, randomized trial

Abstract: Background & aims: Protein-energy wasting (PEW) is increasingly becoming a clinical problem in maintenance hemodialysis patients and guidelines call for nutritional interventions. Serum prealbumin (transthyretin) represents a critical nutritional marker positively correlated with patient survival and negatively correlated with morbidity. Nutritional counseling, oral supplementation as well as intradialytic parenteral nutrition (IDPN) are recommended to fight PEW, however clinical trials on their use are scarce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 20 publications
0
40
1
8
Order By: Relevance
“…Several retrospective and prospective randomized studies have examined the effects of IDPN on clinical end points. Benefits noted included improvements in anthropometric parameters and serum albumin and serum prealbumin albumin levels . One human study that infused stable isotopes to assess muscle turnover during IDPN identified increases in regional and total body protein synthesis .…”
Section: Evidence Supporting the Use Of Idpnmentioning
confidence: 99%
“…Several retrospective and prospective randomized studies have examined the effects of IDPN on clinical end points. Benefits noted included improvements in anthropometric parameters and serum albumin and serum prealbumin albumin levels . One human study that infused stable isotopes to assess muscle turnover during IDPN identified increases in regional and total body protein synthesis .…”
Section: Evidence Supporting the Use Of Idpnmentioning
confidence: 99%
“…In der Normalbevölkerung käme bei Erfolglosigkeit der bisherigen Maßnahmen als nächste Stufe die supportive künstliche Ernährung zum Beispiel über eine PEG-Sonde, welche einen wenn auch kleinen -Eingriff erfordert. Diese Maßnahme ist auch für Dialysepatienten in den EBPG [13] Für die intradialytische parenterale Ernährung konnte Marsen [15] im Vergleich zur Ernährungsberatung allein einen deutlichen Anstieg von Präalbuminals Surrogatparameter für einen gebesserten Ernährungsstatusinnerhalb 16 Wochen zeigen. Die Metaanalyse von Bossola et al [16] bescheinigte der IDPE eine Zunahme von Gewicht, Lean Body Mass, Serumalbumin und Serumpräalbumin.…”
Section: Resultsunclassified
“…IDPN is not to be intended as a long‐lasting therapy; in fact, ONS should be restarted and IDPN should be discontinued as soon as possible based on the combination of three of the following criteria: stable serum albumin >3.8 mg/dL for 3 months; improvement in subjective global assessment (SGA) score to A (well‐nourished) or B (moderately malnourished); clinical examination of improved nutritional status; increase in protein and energy oral intake to >1.0 g/kg/d and to >30 kcal/kg/d . Despite the lack of studies demonstrating any benefit of IDPN on mortality, there is convincing evidence about its positive effects on nitrogen balance, anthropometric parameters and serum prealbumin, a surrogate parameter for hard outcomes in malnourished hemodialysis patients . Such early benefits of IDPN can be identified as soon as after 1 month of treatment when prealbumin is monitored .…”
Section: Nutritional Needs In Esrd Patientsmentioning
confidence: 99%
“…Despite the lack of studies demonstrating any benefit of IDPN on mortality, there is convincing evidence about its positive effects on nitrogen balance, anthropometric parameters and serum prealbumin, a surrogate parameter for hard outcomes in malnourished hemodialysis patients . Such early benefits of IDPN can be identified as soon as after 1 month of treatment when prealbumin is monitored . A recent but small, randomized, controlled trial designed to evaluate the efficacy of IDPN therapy in malnourished patients with refractory anemia suggested an improvement in nutritional status assessed by the malnutrition inflammation score (MIS), BMI and albumin, as well as an improvement in refractory anemia .…”
Section: Nutritional Needs In Esrd Patientsmentioning
confidence: 99%
See 1 more Smart Citation